Implementing Cooperative Script Type of Cooperative Learning Model To Improve Students’ Activeness in Learning Social Studies - Damayanti, Alfiani (International Journal Pedagogy of Social Studies, 2018)
Students’ activeness in learning is the physical and mental involvement of students in earnest in following the learning activities. Students’ activeness is needed in Social Studies so that students not only master the material, but have a provision of useful skills according to Social Studies objectives. This research is motivated by the discovery of some indications of low students' participation in learning Social Studies in class VII 2 SMP Negeri 30 Bandung. The indications are found that students do not pay attention to the teachers or students who are talking, the students do not want to appear in front of their friends, the students only write one to two sentences only in doing the task, and the absence of students who actively ask or respond to the stimulus provided by the teacher. Overcoming these problems, researchers apply a cooperative script type of cooperative learning model as one of the learning method to improve student learning activity. This research uses Classroom Action Research method with Kemmis and Mc Taggart model which carried out three cycles. In cycle 1, the enhancement of students' participation in learning can be categorized as "Enough". There are still many students who do not follow the learning activities thoroughly. In cycle 2, the result of enhancement instudents' participation in learning by being in "Good" category. Although already included in the category "Good" but there are still some students who have not followed the learning activities to the maximum. In cycle 3, students' participation in learning has improved by being in the "Good" category and all students have followed every learning activity thoroughly. The conclusion of this research is the implementing cooperative script type of cooperative learning model can improve students’ activeness in Social Studies.